The nature of the British soldier : warrior or weapons platform a philosophical framework - McCormack, P J (Cranfield University, 2016)
This thesis is an examination of how the nature of the British soldier is constructed/imagined in contemporary British society if a spectrum of meaning is imagined that posits a warrior existing at one extreme and a weapons platform at the other. Located within a philosophical setting and indebted to Charles Taylor’s modern social imaginaries, a number of sub-questions function as the mechanism used to explore the thesis question in the six research chapters which are: 2, Identity and Narrative; 3, Being and Doing; 4, Clausewitz, Trinitarian War and New Wars; 5, Selected Societal Factors (Death, Risk, and Post-heroicand Feminised Society); 6, The Future Nature of Conflict; and 7, Future Technology. This thesis provides a basis by which to evaluate the cultural, practical, philosophical and intellectual pressures affecting how the British soldier is envisaged in the UK social imaginary. It also offers a functional framework to understand those roles British society is prepared to tolerate and validate when deploying and utilising the generic soldier. The main conclusions of the research chapters are contained in the following six propositions: 1. The identity of the warrior requires a narrative of war(fare) validated by the society with whom he/she is in relationship. The identity of the soldier does not necessarily require a narrative of war. 2. The distinction between the warrior and the soldier is best framed in the language of ‘being’ and ‘doing’. For the warrior their ‘being’ is intuited in combat; whereas the soldier requires a narrative that validates the required/expected output. 3. New wars are non-Clausewitzian. Any Western narrative will suffer narrative deflation in the soldier’s daily experience in non-Western operational settings. 4. Post-modern, risk averse, post-heroic societies will struggle to generate a nonapocalyptic narrative capable of tolerating significant casualty numbers. 5. The question of intervention in a non-Western, non-permissive operational setting will examine the depth of liberal values in Western societies. 6. Though pragmatic, the development of robotic weapons stands in contradiction to the authenticity of the warrior and robs the West of the vitality of its liberal values.
Keywords: Military covenent; Military perception; Philosophy